Comprehensive assessment of the psychological well-being of school going adolescent girls in Chandigarh, India - Singh, Chandni; Walia, Dinesh K.; Prashar, Savita (International Journal Of Community Medicine And Public Health, 2024)
Background: Adolescence, a crucial stage in human development, involves significant physical and psychological changes. Unfortunately, these transformations often go unnoticed, leading to an increase in psychological issues among adolescents. Objective of the study was to have a comprehensive assessment of the reasons due to which the adolescents are suffering from high psychological distress in school-going adolescent girls in Chandigarh. Methods: A cross-sectional study was conducted in Chandigarh schools included 168 adolescent females aged 13 to 19. The data collection utilized a multi-stage random sampling approach. Results: The research revealed that academic pressure 147 (87.5%), financial concerns of the family 77 (45.8%), difficulties in communication with family and peers 86 (51.2%) and the negative thinking pattern (83.4%, n=140) are affecting the adolescent girls' mental well-being. The study revealed that a significant number of participants frequently experienced emotions such as nervousness, guilt, social anxiety, insecurity, discrimination, and difficulty concentrating. Additionally, a substantial portion of the group reported instances of sleeplessness 92 (54.8%) and feelings of loneliness 136 (81%). Participants also indicated engaging in coping mechanisms like over thinking, procrastination, and overeating when facing stress. Alarmingly, some individuals turned to smoking, alcohol consumption, and drug abuse as stress-relief strategies, raising concerns for the community. Conclusions: The study highlighted the fact that supportive environment at home and in schools, with open communication and counseling to address these issues. Work should be done to reduce the stigma associated with mental health issue and encourage open conversations about mental health to help adolescents feel more comfortable seeking support.